1995
DOI: 10.1002/glia.440150402
|View full text |Cite
|
Sign up to set email alerts
|

Strain differences in the distribution of NDP‐ase labelled microglia in the normal rabbit retina

Abstract: Nucleoside diphosphatase (NDP-ase) labelled microglial cells were examined in retinas of three strains of rabbit, the New Zealand White (albino), the Canberra Half-Lop, and the Dutch Belted. The distribution in the nerve fibre and inner plexiform layers was similar in all strains. However, the outer plexiform layer (OPL) of Dutch-Belted rabbits was completely covered with a population of non-overlapping NDP-ase positive microglia while the OPL of New Zealand White and Half-Lop strains contained only occasional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…We have recently demonstrated that different strains of rabbit have quite different numbers of NDP-ase positive microglia in the OPL, ranging from a complete coverage to only rare cells, as in the strain used in the current study (Humphrey and Moore, 1995). Labelling with Griffonia simplicifolia lectin produced similar results but we do not know whether these are independent markers and therefore, although unlikely, there could be a population of microglia that do not express NDP-ase.…”
Section: Opl Microgliasupporting
confidence: 78%
“…We have recently demonstrated that different strains of rabbit have quite different numbers of NDP-ase positive microglia in the OPL, ranging from a complete coverage to only rare cells, as in the strain used in the current study (Humphrey and Moore, 1995). Labelling with Griffonia simplicifolia lectin produced similar results but we do not know whether these are independent markers and therefore, although unlikely, there could be a population of microglia that do not express NDP-ase.…”
Section: Opl Microgliasupporting
confidence: 78%
“…In 77% of the retinas analysed, there were regions where microglial cells clustered together, covering all layers of the retina. These accumulations have been described by others (Humphrey and Moore, 1994, 1995; reviewed by: Kreutzberg, 1996, Moore and Thanos, 1996) and have been called microglial nodes (Fig. 2F).…”
Section: Resultsmentioning
confidence: 61%
“…This pattern of distribution is similar to that in different species of adult mammals (Boycott and Hopkins, 1981;Hume et al, 1983;Sanyal and De Ruiter, 1985;Boya et al, 1987;Penfold et al, 1991;Provis et al, 1995;Humphrey and Moore, 1995;Thanos et al, 1996). The retinal microglia have an exogenous origin (Ashwell, 1989;Ashwell et al, 1989;Schnitzer, 1989;Diaz-Araya et al, 1995a,b;Navascués et al, 1995Navascués et al, , 1996.…”
Section: Introductionsupporting
confidence: 51%